INFLUENCE OF METEOROLOGICAL ELEMENTS IN ACCIDENTS IN ENTERPRISES WITH RADIOACTIVE ELEMENTS OR DANGEROUS CHEMICAL SUBSTANCES IN BULGARIA (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2023)
In the analysis of the meteorological elements that influence the spread of radioactive particles, radioactive isotopes and dangerous chemical substances on the territory of Bulgaria, the winds and air currents that form in the airspace over Bulgaria are considered. These are the main meteorological elements that most strongly influence the change in the radioactive background. Another element that has an impact is precipitation in its various manifestations - horizontal and vertical in appearance and depending on the aggregate state of the water. Due to their negligible influence on the radiation environment, we will exclude the remaining meteorological elements from the factors forming the natural indicators of the state of the atmosphere, water and soil. Their influence in areas where there are located large enterprises working with such substances is presented.The report examines the influence of the main factor - the movement of air masses at different altitudes in the atmosphere in the Ludogorie region and the Danube River as an area where NPPs are located in Bulgaria and Romania and which, in the event of an accident, would cause the greatest consequences. The winds in 3 cities from this region, which are located near these enterprises, are described and the corresponding analysis is made.